2020
DOI: 10.1097/tp.0000000000003158
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of En Bloc Transplantation of Small Pediatric Kidneys in Children

Abstract: Background: En bloc transplantation of small pediatric kidneys in children may help expand the existing deceased donor pool; however, studies examining the long-term outcomes of en bloc transplantation in children are few.Methods: We used the Scientific Registry of Transplant Recipients to identify 149 pediatric en bloc recipients transplanted from 10/1/1987-12/31/2017. We used propensity scores to match 148 en bloc with 581 non-en bloc deceased donor recipients (matching variables: transplant age, gender, rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Kizilbash et al . [8] found that recipients of paediatric en bloc transplants had superior 10 year patient (89% vs. 80%; P : 0.04) and graft survival (52% vs. 40%; P : 0.04) compared with matched nonen bloc recipients. After multivariate adjustment, en bloc transplantation was associated with superior patient survival compared to remaining on the wait list (aHR 0.58; 95% CI 0.36–0.95; P : 0.03).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kizilbash et al . [8] found that recipients of paediatric en bloc transplants had superior 10 year patient (89% vs. 80%; P : 0.04) and graft survival (52% vs. 40%; P : 0.04) compared with matched nonen bloc recipients. After multivariate adjustment, en bloc transplantation was associated with superior patient survival compared to remaining on the wait list (aHR 0.58; 95% CI 0.36–0.95; P : 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Kizilbash et al . [8] demonstrated that the higher risk of graft loss due to thrombosis during the first year post‐transplant amongst en bloc recipients was only seen in the earliest era of their study from 1987 to 1997. From 1998 to 2017, there was no difference in 1‐year graft survival between en bloc and standard criteria donor kidney recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a survival benefit for SPD en bloc transplantation compared with remaining on the waiting list (adjusted hazard ratio, 0.58; P50.03). Stratified analysis showed that 1-year graft survival was lower in en bloc recipients transplanted during 1987-1997 but was similar thereafter (10). Other recent pediatric studies have also shown favorable graft survival in pediatric en bloc SPD recipients (11).…”
Section: En Bloc Transplantation Of Small Pediatric Donorsmentioning
confidence: 90%
“…SPDs currently receive high KDPI scores (median KDPI, 72%) (10) and this scoring should be considered for revision because a high KDPI score results in these kidneys being considered primarily for adults. Based on the data discussed above, we advocate increased allocation of SPDs to children.…”
Section: En Bloc Transplantation Of Small Pediatric Donorsmentioning
confidence: 99%
“…These small kidneys are often transplanted “en bloc”: two kidneys along with a part of the donor aorta and vena cava. Having the potential to grow along with a growing recipient, small pediatric kidneys show a good long‐term outcome when transplanted in older children or adult recipients 5 . However, in small pediatric recipients, this procedure shows a high incidence of vascular complications.…”
Section: Epidemiologymentioning
confidence: 99%